Antioxidative behavior of a novel samarium complex in styrene-butadiene rubber/silica composites. (November 2016) - Zou, Yongkun; Sun, Yangkun; Zhang, Yunlong; He, Jingwei; Tang, Zhenghai; Zhu, Lixin; Luo, Yuanfang; Liu, Fang
Abstract: The focus of this study was on the thermo-oxidative aging resistance of a new rare earth complex, samarium lysine dithiocarbamate (Sm-LDC), in the styrene-butadiene rubber (SBR)/silica composites. The anti-aging behavior of SBR/silica composites with Sm-LDC, as well as several common commercial antioxidants, was systematically investigated by oxidation induction time (OIT), mechanical testing, crosslink density determination, Fourier transform infrared spectroscopy with attenuated total reflectance (FTIR-ATR), and thermo-gravimetric analysis (TGA). The results demonstrated that Sm-LDC significantly improve the thermo-oxidative stability of SBR/silica composites and protect the composites against the thermo-oxidative aging more effectively than the widely used antioxidant 4010NA and antioxidant MB in rubber industry. It could be attributed to the synergistic effect between dithiocarboxyl groups and samarium ions in Sm-LDC, which can high-efficiently decompose the hydroperoxide and scavenge the oxy radicals, respectively. Besides, the results of whiteness and yellowness index ( Y.I. ) analysis indicated that Sm-LDC can hardly cause discoloration to the SBR/silica composites and is better than the recognized light-colored antioxidant MB in the aspect of color. This research might open up new opportunities for preparing highly thermo-oxidative aging-resistant rubber composites without color contamination.